Genome‐wide analysis of the oxyntic proliferative isthmus zone reveals ASPM as a possible gastric stem/progenitor cell marker over‐expressed in cancer. Issue 4 (26th August 2015) - Vange, Pål; Bruland, Torunn; Beisvag, Vidar; Erlandsen, Sten Even; Flatberg, Arnar; Doseth, Berit; Sandvik, Arne K; Bakke, Ingunn
Abstract: The oxyntic proliferative isthmus zone contains the main stem/progenitor cells that provide for physiological renewal of the distinct mature cell lineages in the oxyntic epithelium of the stomach. These cells are also proposed to be the potential cells‐of‐origin of gastric cancer, although little is known about their molecular characteristics and specific biological markers are lacking. In this study, we developed a method for serial section‐navigated laser microdissection to isolate cells from the proliferative isthmus zone of rat gastric oxyntic mucosa for genome‐wide microarray gene expression analysis. Enrichment analysis showed a distinct gene expression profile for the isthmus zone, with genes regulating intracellular processes such as the cell cycle and ribosomal activity. The profile was also related to stem cell transcriptional networks and stomach neoplasia. Genes expressed uniquely in the isthmus zone were associated with E2F transcription factor 1 (E2F1), which participates in the self‐renewal of stem cells and in gastric carcinogenesis. One of the unique genes was Aspm [Asp (abnormal spindle) homologue, microcephaly‐associated ( Drosophila )]. Here we show ASPM in single scattered epithelial cells located in the proliferative isthmus zone of rat, mouse and human oxyntic mucosa, which do not seem to be actively dividing. The ASPM‐expressing cells are mainly mature cell marker‐deficient, except for a limited overlap with cells with neuroendocrine and tuft cell features. Further, both ASPM and E2F1 were expressed in human gastric cancer cell lines and increased and correlated in human gastric adenocarcinomas compared to non‐tumour mucosa, as shown by expression profile analyses and immunohistochemistry. The association between ASPM and the transcription factor E2F1 in gastric tissue is relevant, due to their common involvement in crucial cell fate‐regulatory mechanisms. Our results thus introduce ASPM as a novel possible oxyntic stem/progenitor cell marker that may be involved in both normal gastric physiology and gastric carcinogenesis. © 2015 Authors. Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.